Autonomic nervous system - Buijs, Ruud M.; Swaab, D. F. (Dick Frans) (Edinburgh ; London ; New York ; Oxford ; Philadelphia ; St. Louis ; Sydney ; Toronto : Elsevier, 2013)
"The autonomic nervous system controls all involuntary actions within the human nervous system. Core body functions regulated by the autonomic system include breathing, heartbeat, blood pressure, body temperature, perspiration, and bowel, bladder and sexual function. Our understanding of the neurotransmitters associated with the autonomic nervous system has expanded over the past 15 years associated with current research efforts and are now impacting the diagnosis and treatment of autonomic nervous system disorders by clinical neurologists"-- Publisher's description
Includes bibliographical references and index
1 13
Keywords: Autonomic Nervous System Diseases -- physiopathology; Autonomic nervous system -- Diseases; Autonomic Nervous System -- physiopathology; Neurotransmitter Agents -- diagnostic use